2015
DOI: 10.3109/02770903.2015.1089277
|View full text |Cite
|
Sign up to set email alerts
|

The association of childhood asthma with mental health and developmental comorbidities in low-income families

Abstract: This study found mental and developmental adverse consequences of childhood asthma in low-income families. Identifying and treating asthma at an early age could reduce the burden of comorbidities in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The association between psychosocial problems and the self-report of asthma symptoms found in our study demonstrated that the prevalence was greater among children who also reported feelings of loneliness and sleep difficulties and had fewer than three friends as well as children with truancies, with the strongest associations for self-reported feelings of loneliness and sleeping problems. These results are in line with the literature on the relationship between child mental health and asthma [13,35,38]. Studies have examined the relationship between child mental health problems and chronic diseases; however, the results have been controversial [39].…”
Section: Discussionsupporting
confidence: 88%
“…The association between psychosocial problems and the self-report of asthma symptoms found in our study demonstrated that the prevalence was greater among children who also reported feelings of loneliness and sleep difficulties and had fewer than three friends as well as children with truancies, with the strongest associations for self-reported feelings of loneliness and sleeping problems. These results are in line with the literature on the relationship between child mental health and asthma [13,35,38]. Studies have examined the relationship between child mental health problems and chronic diseases; however, the results have been controversial [39].…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that the prevalence of behavioral problems in children with asthma was 37.39%, which was much higher than 18.69% of children without asthma. A previous study of Arif et al [17] reported that behavioral problems were about twice as common in children with asthma as in children without asthma. Blackman also reported the similar results [18].…”
Section: Discussionmentioning
confidence: 93%
“…All independent variables were selected based on their significant association with asthma diagnosis and some disabilities reported in previous studies. 8,9,[12][13][14][15] JAMA Network Open | Pulmonary Medicine Estimated Prevalence of Asthma in US Children With Developmental Disabilities…”
Section: Covariatesmentioning
confidence: 99%